Constructing the Concept of Commissioner Judge in Enforcing the Exclusionary Rules Principle in Indonesia - Febryan Alam Susatyo; Muksin, Muchlas Rastra Samara (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Pretrial aims to protect human rights from misuse of authority by law enforcement officials. The concept of commissioner judges, which aims to be a substitute for the current pretrial procedure. It is expected to achieve the objectives of criminal procedural law that respects human rights by upholding the exclusionary rules principle. This study aims to understand the role of the commissioner judge in upholding the principle of exclusionary rules to achieve a criminal legal process that respects human rights. Further, a normative approach used statutory, conceptual, and comparative legal approaches. The author tries to discover the concept of a commissioner judge upholding the exclusionary rules principle to assess the validity of evidence obtained by law enforcement officials. It is hoped that the objectives of criminal procedure law that protect and guarantee the interests of human rights can be achieved by the concept of commissioner judge.